Prostate cancer molecular imaging standardized evaluation (PROMISE): proposed miTNM classification for the interpretation of PSMA-ligand PET/CT - Eiber, Matthias; Giesel, Frederik L. (Journal of nuclear medicine, 2018)
Prostate-specific membrane antigen (PSMA)-ligand PET imaging provides unprecedented accuracy for whole-body staging of prostate cancer. As PSMA-ligand PET/CT is increasingly adopted in clinical trials and routine practice worldwide, a unified language for image reporting is urgently needed. We propose a molecular imaging TNM system (miTNM, version 1.0) as a standardized reporting framework for PSMA-ligand PET/CT or PET/MRI. miTNM is designed to organize findings in comprehensible categories to promote the exchange of information among physicians and institutions. Additionally, flowcharts integrating findings of PSMA-ligand PET and morphologic imaging have been designed to guide image interpretation. Specific applications, such as assessment of prognosis or impact on management, should be evaluated in future trials. miTNM is a living framework that evolves with clinical experience and scientific data.